Learning through Practice: How Can We Address Loneliness among Older People?. Issue 5 (19th October 2020) - Devine, Paula; Montgomery, Lorna; Cowden, Mandy; Murphy, Fiona
Abstract : The rising incidence of loneliness and social isolation, especially among older people has increasingly been identified in research, practice and policy developments. These issues have become key concerns for public health and social care agendas. Although social isolation and loneliness are often conflated, they are not significantly correlated. The effects of loneliness and social isolation on physical, mental and emotional wellbeing are well documented. Addressing the causes and consequences of loneliness and social isolation is complex. This article outlines a practice example of a grassroots early intervention project seeking to alleviate loneliness and isolation in one community in Belfast, Northern Ireland. CLARE (Creative Local Action Responses and Engagement), a not for profit community interest company, provides a community-based response for isolated older people. The CLARE model encompasses community development worker roles and the skills of community social workers to support and grow community assets, including a vibrant volunteer base. CLARE demonstrates the effectiveness of a multi-dimensional model that addresses loneliness by encompassing three core areas of 'foundation services' as highlighted by the Campaign to End Loneliness. The strengths and challenges of these interventions, and their potential for addressing loneliness and social isolation are discussed.